2014
DOI: 10.1071/hi13033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and antimicrobial susceptibility pattern of hospitalised patients with community-acquired urinary tract infections at a regional hospital in Taiwan

Abstract: Background Community-acquired urinary tract infection (UTI) is the most common bacterial infection encountered at hospitals. Effective empirical antibiotic therapy relies on updated epidemiological data. Aim We described the epidemiology of patients with urosepsis presenting to a community hospital in Taiwan in order to assess the appropriateness of empirical therapy. Methods Retrospective cohort study of hospitalized adult patients with UTI from January 1 to December 31 in 2010. The clinical and microbiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…5e10 The emergence of antimicrobial resistance is of particular concern with respect to urinary tract infections (UTIs), since the majority of causative agents are Gram-negative bacteria. 11 This adds further value to endeavours that aim to understand the burden of UTIs and interventions to reduce their incidence.…”
Section: Introductionmentioning
confidence: 99%
“…5e10 The emergence of antimicrobial resistance is of particular concern with respect to urinary tract infections (UTIs), since the majority of causative agents are Gram-negative bacteria. 11 This adds further value to endeavours that aim to understand the burden of UTIs and interventions to reduce their incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Reports were informed by data collected since 1989 20 –2017. 21 22 The studies were conducted in Argentina, 16 Bangladesh, 23 24 Belgium, 25 Brazil, 26 27 Canada, 28 29 China, 21 30–32 Egypt, 33 Finland, 34 France, 35–37 Germany, 37 Greece, 38 Guyana, 22 India, 39 Italy, 37 40 Israel, 28 41–43 Japan, 44 Korea, 45 46 Madagascar, 47 Nepal, 48 Netherlands, 15 Norway, 49 Pakistan, 50 Poland, 51 Singapore, 20 52 53 Spain, 37 54–57 Sweden, 34 58 USA, 37 59–75 Taiwan 76 77 and Thailand. 78 …”
Section: Resultsmentioning
confidence: 99%
“…Ampicillin, ampicillin/sulbactam, fluoroquinolone are regarded as alternative treatment choices [ 24 ]. Previous study results showed that E. coli has lower susceptibility rates for trimethoprim-sulfamethoxazole (49%), ampicillin (30%), ampicillin/sulbactam (34%), but high susceptibility rate (81%) for cefazolin [ 25 ]. In our study, we had confidence for cefazolin efficacy due to high susceptibility rate record (>80%) against E. coli in our hospital experience.…”
Section: Discussionmentioning
confidence: 99%